Anatomia microscópica do canal carótico e suas relações com a cóclea e a cavidade timpânica - Penido, Norma de Oliveira [UNIFESP] (2005)
The knowledge of the relations between the noble and vital structures of temporal bone is still a great challenge for the otologic surgeon. The microscopic anatomic studies of the temporal bone are one of the greatest help to prevent lesions during surgical intervention. AIM: To study the anatomic correlations between the carotid canal and the cochlea, and the occurrence of dehiscence of the carotid canal in the middle ear tympanic cavity. MANTERIAL AND METHODS: Microscopic study of 122 human temporal bones. RESULTS: The average distance between the carotid canal and the cochlea were: the shortest distance, 1.05mm; basal turn, 2.04mm; middle turn, 2.32mm; and apical turn, 5.70mm. The occurrence of dehiscence of the carotid canal inside the tympanic cavity was 35.2%. CONCLUSION: The small distances between the cochlea and carotid canal, and the high incidence of dehiscence in the tympanic cavity remind us that anatomical knowledge of the temporal bone is required for the best qualification of otologists.